Integrating Positive Discipline and Digital Learning to Improve the Effectiveness of the Indonesian Education Curriculum - Sukariasih, Luh; Erniwati, Erniwati; Ute, Nilawati; Takda, Amiruddin (FKIP Universitas Lampung, 2024)
Integrating Positive Discipline and Digital Learning to Improve the Effectiveness of the Indonesian Education Curriculum. Objectives: This study analysis the effectiveness of implementing a positive discipline approach and digital learning interactions in implementing the Merdeka Curriculum at SMA Negeri 1 Kendari. Methods: Using a qualitative descriptive approach, the research was conducted in the even semester of the 2023/2024 academic year involving 74 educators. Data collection was done through observation, questionnaires, and documentation, with analysis using the Miles and Huberman model. Findings: The results showed that 70% of teachers successfully implemented positive reinforcement effectively, while in digital learning, 85% of teachers successfully implemented the think-pair-share method. The integration of these two approaches creates a more comprehensive learning environment and supports the development of 21st century competencies. The Merdeka Mengajar platform plays an important role as a supporting infrastructure that facilitates the implementation of both approaches. However, the study also identified challenges such as consistency of implementation and the need to develop teachers' digital competencies. Conclusion: The findings present important insights for the development of educational practices in the digital era and the effective implementation of Merdeka Curriculum. Keywords: Positive discipline, digital learning, Merdeka CurriculumDOI: http://dx.doi.org/10.23960/jpp.v14.i3.2024143